Digital transformation in school management: the legacy that strategic actions in the 2020s leave for future pandemics - de Almeida Barbosa Franco, Jacqueline [UNESP]; Espuny, Maximilian [UNESP]; da Motta Reis, José Salvador [UNESP]; Diogo, Gabriel Miranda Monteiro [UNESP]; Paes, Luis Alberto Bertolucci [UNESP]; Costa, Ana Carolina Ferreira [UNESP]; Nunhes, Thaís Vieira [UNESP]; Barbosa, Luís César Ferreira Motta; Rodrigues, Andréia Marize [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP]; de Oliveira, Otávio José [UNESP] (FapUNIFESP (SciELO), 2022)
With the outbreak of social withdrawal due to the pandemic, many countries have undergone drastic transformations in various spheres. In education, face-to-face classes were transformed into distance learning. However, this sudden change caused several problems for students and teachers. Given these events, the purpose of this article was to propose exceptional actions to improve the transition from face-to-face classes to virtual classes. For this, the elements that positively and negatively impacted education in the Covid-19 pandemic were identified in the literature. These elements were then clustered into four strategies, these being: redesign of pedagogical practices, psychological and social support, technological infrastructure in virtual teaching, and school management to cope with the pandemic scenario. The multiple case study method was used, investigating five technical schools located in the state of São Paulo (Brazil). With this, it was possible to propose 10 exceptional actions aimed at the transition from face-to-face classes to virtual classes. The main novelty of this article was the proposition of actions to motivate the school community against the impacts of the pandemic, building memory in its agents, making them more prepared for unexpected events.
Keywords: Distance learning; Pandemic; School management; Social distancing; Strategies